T lymphocytes induce human cancer cells derived from solid malignant tumors to secrete galectin-9 which facilitates immunosuppression in cooperation with other immune checkpoint proteins - Stephanie Schlichtner; Inna M Yasinska; Gurprit S Lall; Steffen M Berger; Sabrina Ruggiero; Dietmar Cholewa; Nijas Aliu; Bernhard F Gibbs; Elizaveta Fasler-Kan; Vadim V Sumbayev (Journal for ImmunoTherapy of Cancer)
Background Galectin-9 is a member of the family of lectin proteins and crucially regulates human immune responses, particularly because of its ability to suppress the anticancer activities of T lymphocytes and natural killer cells. Recent evidence demonstrated that galectin-9 is highly expressed in a wide range of human malignancies including the most aggressive tumors, such as high-grade glioblastomas and pancreatic ductal adenocarcinomas, as well as common malignancies such as breast, lung and colorectal cancers. However, solid tumor cells at rest are known to secrete either very low amounts of galectin-9 or, in most of the cases, do not secrete it at all. Our aims were to elucidate whether T cells can induce galectin-9 secretion in human cancer cells derived from solid malignant tumors and whether this soluble form displays higher systemic immunosuppressive activity compared with the cell surface-based protein.Methods A wide range of human cancer cell lines derived from solid tumours, keratinocytes and primary embryonic cells were employed, together with helper and cytotoxic T cell lines and human as well as mouse primary T cells. Western blot analysis, ELISA, quantitative reverse transcriptase-PCR, on-cell Western and other measurement techniques were used to conduct the study. Results were validated using in vivo mouse model.Results We discovered that T lymphocytes induce galectin-9 secretion in various types of human cancer cells derived from solid malignant tumors. This was demonstrated to occur via two differential mechanisms: first by translocation of galectin-9 onto the cell surface followed by its proteolytic shedding and second due to autophagy followed by lysosomal secretion. For both mechanisms a protein carrier/trafficker was required, since galectin-9 lacks a secretion sequence. Secreted galectin-9 pre-opsonised T cells and, following interaction with other immune checkpoint proteins, their activity was completely attenuated. As an example, we studied the cooperation of galectin-9 and V-domain Ig-containing suppressor of T cell activation (VISTA) proteins in human cancer cells.Conclusion Our results underline a crucial role of galectin-9 in anticancer immune evasion. As such, galectin-9 and regulatory pathways controlling its production should be considered as key targets for immunotherapy in a large number of cancers.